La Nouvelle-Zélande : Vers une nouvelle insertion dans le système alimentaire mondial - Easton, Brian (Études internationales, 1981)
Agricultural products are the source of 75 % of 'New Zealand's export eanings. During the 1970 's, the decline in New Zealand's terms of trade (prices of exports of wool, meat and dairy products having risen more slowly than those of manufactured imports), the loss of access to the British market, the rise of protectionism (notably in the EEC of which Great Britain is a member) have posed serious adjustment problems for New Zealand agriculture. However, the "Marshallien entrepreneur" that is the New Zealand farmer, backed up by the State (which centralises control of exports and credit), has risen to the challenge : as a result, production is being diversified and this has facilitated a re-orientation of exports toward countries outside the OECD area. It is the view of the author that such a policy in conformity with the concept of free-trade, permits a more optimistic outlook for the 1980 's.